Synthesis of 5, 6‐dihydro‐4H‐benzo[d]isoxazol‐7‐one and 5, 6‐dihydro‐4H‐isoxazolo[5, 4‐c]pyridin‐7‐one Derivatives as Potential Hsp90 Inhibitors. (30th April 2015) - Musso, Loana; Cincinelli, Raffaella; Giannini, Giuseppe; Manetti, Fabrizio; Dallavalle, Sabrina
Abstract : A novel class of 5, 6‐dihydro‐4 H ‐benzo[ d ]isoxazol‐7‐ones and 5, 6‐dihydro‐4 H ‐isoxazolo[5, 4‐ c ]pyridin‐7‐ones was designed, synthesized, and assayed to investigate the affinity toward Hsp90 protein. The synthetic route was based on a 1, 3‐dipolar cycloaddition of nitriloxides, generated in situ from suitable benzaldoximes, with 2‐bromocyclohex‐2‐enones or 3‐bromo‐5, 6‐dihydro‐1 H ‐pyridin‐2‐ones. Whereas all the compounds bearing a benzamide group on the bicyclic scaffold were devoid of activity, the derivatives carrying a resorcinol‐like fragment showed a remarkable inhibitory effect on Hsp90. Docking calculations were performed to investigate the orientation of the new compounds within the binding site of the enzyme. Abstract : A series of 5, 6‐dihydro‐4 H ‐benzo[ d ]isoxazol‐7‐ones and 5, 6‐dihydro‐4 H ‐isoxazolo[5, 4‐ c ]pyridin‐7‐ones was designed, synthesized, and assayed to investigate affinity toward Hsp90 protein. Compounds carrying a resorcinol‐like fragment showed a remarkable inhibitory effect on Hsp90. Docking calculations were performed to investigate the orientation of the new compounds within the binding site of the enzyme.